La formation des enseignants recourant aux dispositifs audio-visuels : analyse des configurations d’activité chez des fonctionnaires stagiaires - Lionel Roche; Nathalie Gal-Petitfaux (Recherches en Éducation)
The aim of this article will be to present the way of appropriateness through a case study. A training system for teachers who can have an audio-visual aid. This study contemplates training system using an audio-visual aid and also interaction between an individual, a group and an artefact. We also presents the different types of instrumental mediation developed by the trainee teachers. To succed in this process, we will consider into account the analyses of configurations of activity which means self organized ways of interaction between individual and social and material environment.